Public security vs. private self-protection: optimal taxation and the social dynamics of fear - Angelo Antoci; Pier Luigi Sacco; Mauro Sodini (Fondazione Eni Enrico Mattei (FEEM), 2010)
In this paper, we develop a simple model of social dynamics governing the evolution of strategic self-protection choices of boundedly rational potential victims facing the threat of prospective offenders in a large population with random matching. We prove that individual (and socially transmitted) fear of exposure to criminal threats may actually condition choices even in the face of objective evidence of declining crime rates, and thereby cause the eventual selection of Pareto inefficient equilibria with self-protection. We also show that a suitable strategy of provision of public security financed through discriminatory taxation of self-protective expenses may actually overcome this problem, and drive the social dynamics toward the efficient no protection equilibrium. In our model, we do not obtain, as in Cressman et al. (1998), a crowding-out result such that the net impact of public spending on the actual social dynamics is neutral and the economy keeps on cycling between phases of high and low criminal activity with varying levels of self-protection; quite to the contrary, it can be extremely effective in implementing the social optimum, in that it acts primarily on the intangible dimension, that is, on the social dynamics of fear. We claim that this kind of result calls for more interdisciplinary research on the socio-psycho-economic determinants of fear of crime, and for consequent advances in modelling approaches and techniques.
Keywords: C73; H23; K49; 330; Self-Protection; Fear of Crime; Cultural Selection Dynamics; Replicator Dynamics